The Development of Student Worksheets on Inquiry-Based Plant Growth and Development Sub-Concept - Noorhidayati Noorhidayati; Ina Apriliana; Hardiansyah Hardiansyah (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The concept of plant growth and development is important to learn, through a conceptual, contextual and scientific approach. The results of the analysis of the needs of Biology teachers and grade XII students of SMAN 2 Kintap show that there are still problems in making student worksheet on certain materials. As many as 91% of students are interested in student worksheet which is accompanied by lots of illustrations, concrete pictures, and easy to understand subject matter. Then, as many as 83% who like worksheet which looks colorful and attractive. This development research uses a 4D model which is limited to the Develop stage. This study aims to describe the validity and practicality of the student worksheet subconcept of Inquiry-Based Plant Growth and Development. The research was carried out in grade XII MIA SMAN 2 Kintap and Biology Education Study Program FKIP ULM. The results showed that the student worksheet of the Plant Growth and Development subconcept obtained an average validity score of 97% from 4 aspects of the assessment that were assessed by 3 (three) validators and included very valid criteria (can be used without revision), while practicality obtained a value of 3.8 from the assessment. by 12 (twelve) students, included in the very good criteria, so it is practical to use.Abstrak Konsep pertumbuhan dan perkembangan tumbuhan penting untuk dipelajari, melalui pendekatan konseptual, kontekstual dan ilmiah. Hasil analisis kebutuhan guru Biologi dan peserta didik kelas XII SMAN 2 Kintap menunjukkan bahwa pembuatan LKPD pada materi tertentu masih terkendala. Sebanyak 91% peserta didik tertarik dengan LKPD yang disertai banyak ilustrasi, gambar-gambar yang konkrit, dan mudah memahami materi pelajaran. Lalu, sebanyak 83% yang menyukai LKPD yang tampilannya warna-warni dan menarik. Penelitian pengembangan ini menggunakan model 4D yang dibatasi pada tahap Develop. Penelitian ini bertujuan bertujuan untuk mendeskripsikan validitas dan kepraktisan LKPD subkonsep Pertumbuhan dan perkembangan Tumbuhan Berbasis Inkuiri. Penelitian dilaksanakan di kelas XII MIA SMAN 2 Kintap dan Program Studi Pendidikan Biologi FKIP ULM. Hasil penelitian menunjukkan LKPD subkonsep Pertumbuhan dan Perkembangan Tumbuhan memperoleh skor validitas rata-rata 97% dari 4 aspek penilaian yang dinilai oleh 3 (tiga) validator dan termasuk kriteria sangat valid (dapat digunakan tanpa revisi), sedangkan kepraktisan diperoleh nilai 3,8 dari penilaian oleh 12 (dua belas) peserta didik, termasuk dalam kriteria sangat baik, sehingga praktis untuk digunakan.